Pengembangan Keterampilan Dasar Mengajar Calon Guru Melalui Mata Kuliah Microteaching di STT Blessing Indonesia Makassar - Danny David H. Wurarah; Tri Retno Delpiero Mohama (Sekolah Tinggi Teologi Blessing Indonesia Makassar, 2023)
Education in Indonesia has problems with the quality of education, this is a challenge for teaching staff to advance the quality of education in Indonesia, so that an educator is required to have competence as a professional teacher and become an education pioneer. To see the progress in the competency of prospective teaching staff, this research was then carried out which aims to analyze the basic teaching skills of prospective teachers through the Microteaching course as prospective teaching staff. This research uses a descriptive qualitative method approach, the subjects that will be studied in this research are students of the Blessing Indonesia Makassar Theological College, the VI semester Christian Religious Education study program consisting of 10 students, 2 male students and 8 female students. Then the results were found that the basic teaching skills of students in the sixth semester of the Christian Religious Education Study Program at Blessing Indonesia Makassar Theological College in the Microteaching course had an average score for the achievement aspect with Good criteria. However, the skills for opening and closing lessons have achieved very good criteria.Keywords: Basic Teaching Skills ; Microteaching ; Education Pendidikan di Indonesia memiliki permasalahan pada mutu Pendidikan, ini merupakan suatu tantangan bagi tenaga pendidik untuk memecahkan masalah serta memajukan mutu Pendidikan di Indonesia, sehingga seorang pendidik dituntut agar bisa memiliki kompetensi sebagai seorang guru profesional serta menjadi pelopor Pendidikan. Untuk melihat kemajuan kompetensi calon tenaga pendidik, kemudian dilakukan penelitian ini yang bertujuan untuk menganalisis bagaimana keterampilan dasar mengajar calon guru lewat mata kuliah Microteaching sebagai calon tenaga pendidik. Penelitian ini menggunakan pendekatan metode kualitatif deskriptif, subjek yang akan diteliti dalam penelitian ini yaitu Mahasiswa Sekolah Tinggi Teologi Blessing Indonesia Makassar, program studi Pendidikan Agama Kristen semester VI yang terdiri dari 10 mahasiswa, 2 mahasiswa laki-laki dan 8 mahasiswa perempuan. Kemudian ditemukan hasil bahwa kemampuan dasar keterampilan mengajar mahasiswa semester VI Program Studi Pendidikan Agama Kristen Sekolah Tinggi Teologi Blessing Indonesia Makassar dalam mata kuliah Microteaching memiliki nilai rata-rata aspek capaian dengan kriteria Baik. Namun pada keterampilan membuka dan menutup pelajaran memiliki capaian dengan kriteria Sangat Baik.Kata Kunci : Keterampilan Dasar Mengajar ; Microteaching ; Pendidikan